Monotonic Set-Extended Prefix Rewriting and Verification of Recursive Ping-Pong Protocols - Delzanno, Giorgio; Esparza, Javier; Srba, Jirí (BRICS Report Series, 2006)
Ping-pong protocols with recursive definitions of agents, but without any active intruder, are a Turing powerful model. We show that under the environment sensitive semantics (i.e. by adding an active intruder capable of storing all exchanged messages including full analysis and synthesis of messages) some verification problems become decidable. In particular we give an algorithm to decide control state reachability, a problem related to security properties like secrecy and authenticity. The proof is via a reduction to a new prefix rewriting model called Monotonic Set-extended Prefix rewriting (MSP). We demonstrate further applicability of the introduced model by encoding a fragment of the ccp (concurrent constraint programming) language into MSP.